Drying characteristic of emulsified gelatin film: article - Abdullah, Saarwani; Mohammed Manshor, Norasmah (2017)
Nowadays, the application of edible film is being increased. The biodegradable film is introduced as an alternative way to minimize the uses of the synthetic polymer because it can be eaten and degrade easily. The purpose of this study is to determine drying characteristic of emulsified edible film at different temperatures and to determine the optimum condition for drying. The method used to prepare the film is by casting method. The material or chemicals used to prepare the film are plasticizer (glycerol), protein (gelatin), distilled water and lipids (vegetable oil) which is sunflower oil. The film was dried at different temperature which were 45ºC, 50ºC, 55ºC and 60ºC. The drying of films also an effective ways of prolonging the shelf life by reducing the moisture content of the material that can reduced the microbial growth and enzymatic reaction. It also involved the heat transfer from heating the medium to the product surface. The drying data were fitted to the Newton model, Page model and Henderson and Pabis model. Then, the values of coefficient of determination (R²), mean bias error (MBE) and root mean square error (RMSE) were used to determine the goodness or the quality of the data fitted. Therefore, the Page model showed a better fit to emulsified gelatin film compared to Newton and Page model with appropriate equation ln(-ln MR) = 2.1263 lnt - 4.8658. The optimum temperature of this research was 60ºC